Small Satellites: National Regulatory Challenges - Tūbaitė-Stalauskienė, Asta (Teisė, 2019)
[full article, abstract in English; abstract in Lithuanian]This article analyses the regulation of space activities, especially small satellites activities. Its purpose is to analyse the relevant international legal framework and discuss the possible future national space legislation in Lithuania. It has been divided into two chapters. Chapter 1 summarises the relevant international space law and addresses essential aspects related to the authorisation of space activities, registration of objects launched into outer space, liability issues, insurance requirements and debris mitigation issues. Chapter 2 deals with reasons to adopt the national space legislation in Lithuania and discusses what legal aspects should be covered by the national law in order to guarantee balance between the regulation and promotion of small satellite activities. Finally, it includes the Model Law on the Promotion of National Space Activities and the Establishment of a National Space Registry of the Republic of Lithuania.
Keywords: national space law; international space law; small satellites; National Space Registry